Pengembangan Tes Untuk Mengukur Kemampuan Penalaran Mahasiswa Mata Kuliah Geometri - Nurhasanah Nurhasanah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2018)
The purpose of the research is to develop a test which intentionally used to measure students’ critical ability on the valid Geometry Course. The Research and Development method was employed through the procedure of 4-D model which basically consists of four stages namely; define, design, development, and dissemination. The test is given to students coming from Department of Mathematic Education UNIPA. The finding reveals that there have been forms of final products that are (1) a valid lattice in assessing students’ critical ability on the Geometry Course notably on the subject area of line, angle, triangle deductive reasoning, congruent triangle, Parallel line, distance and number of angle, Parallelograms, Trapezoids, Medians and Midpoints. (2) test to measure students’ critical ability the Geometry Course specifically on area of line, angle, triangle deductive reasoning, congruent triangle, Parallel line, distance and number of angle, Parallelograms, Trapezoids, Medians and Midpoints.